Proceedings of the 2021 ACM SIGIR International Conference on Theory of Information Retrieval 2021
DOI: 10.1145/3471158.3472227
|View full text |Cite
|
Sign up to set email alerts
|

A Discriminative Semantic Ranker for Question Retrieval

Abstract: Similar question retrieval is a core task in community-based question answering (CQA) services. To balance the effectiveness and efficiency, the question retrieval system is typically implemented as multi-stage rankers: The first-stage ranker aims to recall potentially relevant questions from a large repository, and the latter stages attempt to re-rank the retrieved results. Most existing works on question retrieval mainly focused on the re-ranking stages, leaving the first-stage ranker to some traditional ter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Following this, the paper [115] propose a new method for training dense retrieval models by using pseudo-relevance feedback and multiple representations, which allows the model to learn more robust representations of queries. To further improve performance, [116] proposed a new method for training a discriminative semantic ranker for question retrieval. This approach focuses on training the model to differentiate between relevant and non-relevant documents, which is important for accurate retrieval.…”
Section: Dense Retrieval Methodsmentioning
confidence: 99%
“…Following this, the paper [115] propose a new method for training dense retrieval models by using pseudo-relevance feedback and multiple representations, which allows the model to learn more robust representations of queries. To further improve performance, [116] proposed a new method for training a discriminative semantic ranker for question retrieval. This approach focuses on training the model to differentiate between relevant and non-relevant documents, which is important for accurate retrieval.…”
Section: Dense Retrieval Methodsmentioning
confidence: 99%
“…As researchers strive to improve information retrieval, they have developed methods to train models that can effectively distinguish between relevant and non-relevant documents in dense retrieval settings. Cai et al [109] suggested a method for training a discriminative semantic ranker for question retrieval, focusing on this crucial aspect of accurate retrieval. To further refine the understanding of the relationship between passages and queries, Wu et al [110] proposed a representation decoupling method that improves open-domain passage retrieval by separating the encoding of passages and queries.…”
Section: ) Discriminative Semantic Ranking Approaches In Dense Retrievalmentioning
confidence: 99%
“…There are multiple architectures for BERT-based ranking models, including cross-encoder [12], dual encoders [2] and ColBERT [8]. Comparing with other architectures, cross-encoder can achieve the best performance, while its inference latency is the highest comparing with the other ones.…”
Section: Related Workmentioning
confidence: 99%
“…Most of existing approaches [7,[15][16][17]22] for language model distillation aim at improving the performance of student model in general natural language understanding (NLU) tasks [21]. Specially for document retrieval and ranking tasks, some latest approaches are focusing on cross-architecture distillation approaches [5,10] using cross-encoder [12] teachers and ColBERT [8] or dual-encoder [2] based students. For those cross-architecture approaches, both teachers and students are using pre-trained models in the same scale (i.e.…”
mentioning
confidence: 99%